Translating research results in economic terms: An application of economic utility analysis using SDT-based interventions - Gagné, Marylène; Forest, Jacques; Gilbert, Marie-Helene; Beaulieu, Genevieve; LeBrock, P. (Oxford University Press, USA, 2014)
The book covers a wide range of topics, including: how to bring about commitment, engagement, and passion in the workplace; how to manage stress, health, emotions and violence at work; how to encourage safe and sustainable behavior in ...